Debt-Equity Composition of International Investment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
Capital flows to the nonindustrial countries share three striking characteristics. First, the bulk, of these flows was in the form of debt, not equity; second, the loans were mostly to, or guaranteed by, debtor governments; and third, these debts were largely bank loans, not bonds. This paper examines the economic factors that may have been responsible.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet